Establishment of an untransfected human corneal epithelial cell line and its biocompatibility with denuded amniotic membrane - Fan, Ting-Jun (International Journal of Ophthalmology Press, 2011)
AIM: To establish an untransfected human corneal epithelial (HCEP) cell line and characterize its biocompatibility with denuded amniotic membrane (dAM). METHODS: The torn HCEP pieces were primarily cultured in DMEM/F12 media (pH 7.2) supplemented with 20% fetal bovine serum and other necessary factors, yielding an HCEP cell line which was its growth performance, chromosome morphology, tumorigenicity and expression of marker proteins analyzed. In addition, the biocompatibility of HCEP cells with dAM was evaluated through histological and immunocytochemistry analyses and with light, electron and slit-lamp microscopies. RESULTS: HCEP cells proliferated to confluence in 3 weeks, which have been subcultured to passage 160. A continuous untransfected HCEP cell line, designated as utHCEPC01, was established with a population doubling time of 45.42 hours as was determined at passage 100. The cells retained HCEP cell properties as were approved by chromosomal morphology and the expression of keratin 3. They, with no tumorigenicity, formed a multilayer epithelium-like structure on dAMs through proliferation and differentiation during air-liquid interface culture, maintained expression of marker proteins including keratin 3 and integrin β1 and attached tightly to dAMs. The reconstructed HCEP was highly transparent and morphologically and structurally similar to the original. CONCLUSION: An untransfected and non-tumorigenic HCEP cell line was established in this study. The cells maintained expression of marker proteins. The cell line was biocompatible with dAM. It holds the potential of being used for in vitro reconstruction of tissue-engineered HCEP, promising for the treatment of diseases caused by corneal epithelial disorders.